Probabilistic аssessment of the stress–strain state of the drum shaft of a grain‑cleaning separator under fatigue failure conditions (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The paper presents a combined computational and experimental analysis of the shaft of a perforated drum in a grain‑cleaning separator, accounting for static and cyclic loads and the stochastic nature of fatigue failure of welded joints. The object of study is the drum shaft subjected to uniformly distributed and concentrated bending loads from its own weight, the mass of the drum and grain bulk, as well as the driving torque. Evaluation of the stress–strain state of a finite‑element model built in Autodesk Inventor confirmed an adequate margin of static strength for the considered design variants. At the same time, local zones of stress concentration were identified at welded seams, where the safety factor may drop below unity, which is critical under variable loading. Fatigue life calculations were performed using allowable stresses with median S–N curves and a probabilistic assessment that accounts for the distribution of stress amplitudes and the level of residual stresses generated during welding. It is shown that high residual stresses substantially reduce service life, whereas optimization of welding technology aimed at ensuring full penetration and subsequent post‑weld heat treatment significantly increases durability. A set of constructive and technological measures is proposed, including refinement of shaft geometry, application of reinforcing elements in crack initiation zones, preheating, and welding quality control to reduce residual stresses. The results have practical value for the design, modernization, and enhancement of operational reliability of separators in grain processing lines.
Keywords: drum shaft; grain‑cleaning separator; welded joints; fatigue life; stress concentration; residual stresses; S–N curves; probabilistic methods; finite‑element analysis